Analysis of the Application of Dunhuang Pattern Elements in Sustainable Design - Ouyang, Mingjun (Journal of Education and Educational Technologies, 2023)
Dunhuang patterns are an important component of Dunhuang grotto art. Dunhuang patterns are decorated on murals, statues, grotto bodies, and wooden eaves, with exquisite craftsmanship, rich shapes, huge scale, unique layout, and precious artistic value. The character shapes, line sketches, and coloring of Dunhuang patterns express people's desire for beauty and goodness. Through analysis and research on the inheritance and evolution of artistic styles in different periods of Dunhuang patterns, the use of sustainable design concepts for creative transformation and innovative design not only enhances the influence and appeal of excellent traditional Chinese culture represented by Dunhuang culture, but also reveals the cultural spirit contained in Dunhuang patterns. This article explores the application of Dunhuang pattern elements in sustainable design.